2011
DOI: 10.1074/jbc.m110.108001
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aminosaccharide Compound Blocks Immune Responses by Toll-like Receptors and Nucleotide-binding Domain, Leucine-rich Repeat Proteins

Abstract: Toll-like receptors (TLRs) and nucleotide-binding domain, leucine-rich repeat (NLR) proteins are two major forms of innate immune receptors that trigger inflammatory responses by various biological mechanisms such as cytokine production, recruitment of inflammatory cells, or activation of adaptive immunity. Although the innate immune system is designed to fight against infectious pathogens, excessive activation of TLR or NLR signaling pathways may lead to unwarranted inflammation with hazardous outcomes, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, the N -acetyl-glucosamine scaffold has known anti-inflammatory effects in a variety of cells, including retinal pigment epithelial cells [28], endothelial cells [29], mast cells [30] and peritoneal mesothelial cells [31], providing further evidence for the role for this class of molecules as TLR4 inhibitors. Interestingly, Lee and colleagues also recently showed that a novel aminosaccharide has anti-TLR effects in macrophages in vitro [32]. Based on these findings, we submit that per-acylated 2-aminopyranoses with alkyl side chains at the anomeric carbon, in particular those with similarity to our lead compound, C34, have the potential to elicit broad and beneficial clinical effects in diseases characterized by TLR4 hyperactivation.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, the N -acetyl-glucosamine scaffold has known anti-inflammatory effects in a variety of cells, including retinal pigment epithelial cells [28], endothelial cells [29], mast cells [30] and peritoneal mesothelial cells [31], providing further evidence for the role for this class of molecules as TLR4 inhibitors. Interestingly, Lee and colleagues also recently showed that a novel aminosaccharide has anti-TLR effects in macrophages in vitro [32]. Based on these findings, we submit that per-acylated 2-aminopyranoses with alkyl side chains at the anomeric carbon, in particular those with similarity to our lead compound, C34, have the potential to elicit broad and beneficial clinical effects in diseases characterized by TLR4 hyperactivation.…”
Section: Discussionmentioning
confidence: 56%
“…Small-molecule and monoclonal antibody innate immune modulators are under investigation in models of acute lung injury, lentiviral infection, and inflammatory disorders (20,47,48). Eritoran, a small-molecule antagonist of TLR4, an upstream mediator of PTX3 production, is currently under investigation for treating severe sepsis (49).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies thus far have been focused on generating derivatives with a higher level of adjuvant activity, but the development of derivatives that suppress rather than enhance immune responses is also a promising area of study. We recently discovered DFK1012, an anti-inflammatory MDP derivative that acts to suppress proinflammatory cytokine production in macrophages upon stimulation of innate immune receptors such as TLR (Toll-like receptor) or NLR (Nucleotide binding domain, Leucine rich repeats) proteins 137 . Together with these recent findings, the synthetic approaches outlined in this paper will help us diversify the chemical structure of MDP and study the relationship between its structure and function in an effort to optimize its desirable biological activity.…”
Section: Discussionmentioning
confidence: 99%